Social Interaction Anxiety, Social Loneliness, and Mental Health of Online Gamers - Muhammad Rashid Khan (Journal of Peace, Development and Communication, 2024)
With the advent of fast internet young adults have begun to spend more time playing online games than before. This has changed the dynamics of communication between individuals from physical to virtual. It has also given rise to issues of peculiar nature which were scarce before. The current study examined social interaction anxiety and loneliness among individuals who play online games and use online gaming as a primary means of making friends. The study employed 120 students from various academic institutes across Lahore who played a very popular online first-person shooter game i.e., PUBG. This nature of the study was correlational. Our results indicated a positive correlation between age and the number of hours playing online video game. We also found a positive correlation between playing video game and increase in the prevalence gaming disorder among young men. We did not find a significant relationship between loneliness and gaming disorder. This may help in alleviating some of the stigma surrounding online gaming that increased causes loneliness among young men. It may be so that the virtual community which the gamers create may offer a safe haven for likeminded individuals to communicate and bond.